Analisis Faktor-Faktor Yang Mempengaruhi Perkembangan Bisnis Franchise Indomaret di Provinsi Riau - . Bakaruddin; Ardi Qudrotullah (Akuntansi & Ekonomika, 2018)
This study aims to prove empirically the influence of the financial performance of the franchisor company, the franchisor's experience, to the business development of the minimarket franchise Indomaret with local government regulations as a moderating variable. Research conducted at PT. Indomarco Prismatama Riau Region 2018 with a sample of 72 respondents and using the analysis of Moderating Regression Analysis (MRA). The result of the research shows that local government regulation is a moderator variable of the company's financial performance variable to the development of Indomaret franchise business. Local government regulation is a moderator variable of the firm's experience variable on the development of Indomaret franchise business. Local government regulation is a moderator variable of the company's financial performance variable and the company's experience on the development of Indomaret franchise business.